The Rain Dragon Rescue : The Imaginary Veterinary #3 - Selfors, Suzanne; Santat, Dan (New York : Little, Brown and Company, 2014)
"Ten-year-olds Ben and Pearl continue their apprenticeships at Dr. Woo's Worm Hospital, where they meet a dragon named Metalmouth and get a chance to travel to the Imaginary World"--
Keywords: Dragons -- Fiction; Imaginary creatures -- Fiction; Veterinarians -- Fiction; Apprentices -- Fiction